CFD algorithm for moving boundary problems of isothermal drying and shrinkage: Case of prunes - Lentzou Diamanto; Templalexis Charalampos; Boudouvis Andreas G.; Karathanos Vaios; Xanthopoulos Georgios (E3S Web of Conferences)
A moving-boundary FEM model describing isothermal drying of fruit was employed as an inverse problem to estimate water diffusivity and peel resistance, including shrinkage. Water diffusivity and peel resistance were estimated using the Levenberg-Marquardt (L-M) optimisation algorithm based on the experimental drying data. The surface resistance is accounted as the sum of the peel and the diffusive boundary layer resistances, the latter being negligible compared to the former. The estimated peel resistance decreased by 86% as the drying temperature increased from 45 °C to 65 °C and by 44% as the drying temperature increases from 55 °C to 65 °C. The CFD optimisation model efficiently predicted the experimental water content and shrinkage.